Illuminating the chemo-mechanics of hydrogen enhanced fatigue crack growth in aluminum alloys. (November 2015) - Zamora, R.J.; Baker, K.L.; Warner, D.H.
Graphical abstract: Abstract: The presence of elemental hydrogen is known to accelerate fatigue crack growth in aluminum alloys. However, a direct link between experimental data and the governing atomistic mechanisms has remained elusive. Here we present a series of computational studies, across multiple length scales, directly linking an atomistic mechanism to experimental data for a specific aluminum alloy. Starting with an ab initio investigation of hydrogen bonding near the (1 1 1) aluminum surface, we quantify the effects of hydrogen surface impurities on slip and decohesion. We then modify an aluminum-only interatomic potential to reproduce ab initio trends by strategically shielding critical surface bonds in accordance with the environmental exposure level. The strategic shielding approach is used within a coupled atomistic-continuum discrete dislocation framework to predict the effect of hydrogen on near threshold fatigue crack growth rates. The predicted trends agree with published experimental data, suggesting that hydrogen enhanced surface deformation is a key failure mechanism for aluminum alloys in humid environments.